Financial and Non Financial Factors on Going-Concern Opinion - Junaidi Junaidi; Cahyanti Sih Triyatmi; Nurdiono Nurdiono (Bina Nusantara University, 2012)
Company's ability to survive is a fundamental uncertainty faced in the preparation and auditing financial statements. Provision of going-concern opinion on these financial statements the company is still being debated. Public Accountant Professional Standards in section 341 states that the auditor is responsible for evaluating whether there is a major doubt on the ability of entities in the continued survival of the appropriate period of time, not more than one year from the date of the financial statements being audited. This research analyzed the financial and non financial factors that affected the provision of going-concern opinion. This research used samples of 63 companies with 315 observations, taken from years 2005-2009. The logistic regression analysis showed that the company's financial condition variables, mitigating evidence, and disclosure significantly influence the acceptance of going-concern opinion. Enterprise risk was not significant at propensity of going-concern opinion.